The Effect Of Curriculum In Building Creative Nation - Azizah Husin (International Conference on Education and Language (ICEL), 2013)
The goal of this study is to analyze the role of curriculum in developing a creative nation.One of the national education goal is make the student be creative and self help. National ciriculum has important role to reach this goal. Some barriers have been happening nowdays. The barriers are: curriculum overloaded, evaluation system focus on cognitive domain, apply LKS (student work paper) much, teacher still use conventional method. This condition caused student and output be passive, not creative. Creative student can solve the problem, have many alternative in finding  solution, able to think analytic, think flexible,and curiosity Curriculum which had made must be oriented to the student development. Suggestion, government have to make curriculum that  not overloaded and stop practice national examination. By simple curriculum, teachers have time to develop materials, so they can practice Student centre learning correctly, and they aren’t much depend on LKS.If teacher creative, student and output will be creative too.Finally  it reflect in building creative nation.